2022
DOI: 10.1002/pi.6366
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of gemini amphiphiles with symmetric tails in selective solvent

Abstract: Gemini amphiphile is a special type of block copolymers formed by connecting two traditional diblock molecules at hydrophilic head groups through spacers. The special structure makes gemini amphiphiles potentially promising for drug delivery and gene delivery. The self-assembly behavior of gemini amphiphiles with tails of equal length in selective solvent was investigated using the dissipative particle dynamics method. The effects of the size of the hydrophilic head group, interaction parameters, concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…We can find that many small aggregates are formed in the system at the beginning, and as time increases the aggregates bind and transform into more and larger sphere‐like micelles, after which the small sphere‐like micelles aggregate and transform into a bilayer disk; then the edges of the bilayer disk curl and become a bowl‐like micelle, and finally the bowl‐like micelle bends and closes to form a vesicle. Therefore, for surfactin‐like polymers, the formation path of vesicles is in agreement with the previous work about amphiphilic block copolymer 3,38–42 …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We can find that many small aggregates are formed in the system at the beginning, and as time increases the aggregates bind and transform into more and larger sphere‐like micelles, after which the small sphere‐like micelles aggregate and transform into a bilayer disk; then the edges of the bilayer disk curl and become a bowl‐like micelle, and finally the bowl‐like micelle bends and closes to form a vesicle. Therefore, for surfactin‐like polymers, the formation path of vesicles is in agreement with the previous work about amphiphilic block copolymer 3,38–42 …”
Section: Resultssupporting
confidence: 91%
“…Therefore, for surfactin-like polymers, the formation path of vesicles is in agreement with the previous work about amphiphilic block copolymer. 3,[38][39][40][41][42] Effect of interaction parameters a AB and a BS Here, we simulate the effect of interactions between different beads on self-assembly by adjusting the interaction parameters. Figure 4 shows the morphological phase diagrams of the aggregates formed by the surfactin-like polymer at different a AB and a BS at surfactin concentration φ = 0.10.…”
Section: Morphology Of Aggregatesmentioning
confidence: 99%
“…Similar supramolecular assemblies have been observed with gemini amphiphiles that have interparticle associations stabilized by interactions between the hydrophilic interfaces. 31,32 We hypothesize that, analogously, electrostatic interactions between the peptides in the cylinder corona stabilize the supramolecular architecture. Supporting this hypothesis, only spherical particles are observed when onBA5-XTEN2 was assembled with an additional 100 mM NaCl that provides charge screening (Figure S33).…”
Section: Resultsmentioning
confidence: 99%
“…The amphiphilic block copolymers self-assemble to vesicles, in which the hydrophobic segment forms a membrane, and the hydrophilic layer forms the inner and outer surfaces of the vesicle, so these two parts are the focus of designing polymeric vesicles. , Unlike lipid-based vesicles, the stability, permeability, drug encapsulation efficiency and release kinetics of polymeric vesicles can be easily tuned by adjusting the polymer molecular weight via polymer chemistry . According to previous studies, the structure of polymeric vesicle such as membrane thickness and cavity size are related to the length of the hydrophobic block, and these structural parameters will affect the encapsulation efficiency of hydrophobic/hydrophilic nanodrugs and the permeability required for nanodrug release. ,,, In addition, studies have shown that relative block length, solvent composition, and other factors will affect the free energy of the aggregate (such as the interfacial energy between the core and the external solution, the stretching of the core forming blocks, and the repulsive interactions between the corona chains) and then affect the aggregate morphology. , Therefore, we studied the effect on the morphology of the drug-loaded polymeric vesicle by adjusting the length of the hydrophobic block and the concentration of the nanodrug.…”
Section: Resultsmentioning
confidence: 99%
“…The amphiphilic block copolymers self-assemble to vesicles, in which the hydrophobic segment forms a membrane, and the hydrophilic layer forms the inner and outer surfaces of the vesicle, so these two parts are the focus of designing polymeric vesicles. 21,50 Unlike lipid-based vesicles, the stability, permeability, drug encapsulation efficiency and release kinetics of polymeric vesicles can be easily tuned by adjusting the polymer molecular weight via polymer chemistry. 17 According to previous studies, the structure of polymeric vesicle such as membrane thickness and cavity size are related to the length of the hydrophobic block, and these structural parameters will affect the encapsulation efficiency of hydrophobic/hydrophilic nanodrugs and the permeability required for nanodrug release.…”
Section: Effect Of Hydrophobic Block Length and Nanodrugmentioning
confidence: 99%